Profit Under Pressure: Analisis Kinerja, Biaya Operasional, dan Persediaan pada Industri Baja Indonesia 2020–2024 - Siti Nabilla Zahiah Kahyo; Listri Herlina; Ilham Winar Nugroho (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2026)
This study analyzes the extent which firm performance, operating expenses, and inventory affect the net profit of manufacturing issuers in the Indonesian steel sub-sector listed on the Indonesia Stock Exchange (IDX) during 2020–2024. Firm performance is measured using Return on Assets (ROA) and Return on Equity (ROE), operating expenses are represented by the Operating Expenses Ratio (OER), inventory is measured using Inventories Turnover (ITO), and net profit is assessed through the Net Profit Margin (NPM). The research applies a quantitative descriptive method and panel data regression using the Common Effect Model (CEM). Quarterly financial statements from PT Krakatau Steel (KRAS), PT Saranacentral Bajatama (BAJA), and PT Lionmesh Prima (LMSH) were used, totaling 60 observations. The results show that ROA and ROE have a significant positive effect on NPM, indicating that efficient management of assets and equity contributes to higher profitability. Meanwhile, OER and ITO have negative but insignificant effects, suggesting that operating expenses and inventory turnover do not strongly influence net profit in an industry with high fixed costs such as steel. Simultaneously, all variables significantly affect NPM, with an R-Square value of 66.25%, indicating that the research model is able to explain most of the variation in net profit highlighting the importance of asset and equity management in enhancing company profitability.